ULTRASONOGRAPHIC ANATOMY OF THE PATELLAR LIGAMENTS BEFORE ANDAFTER MEDIAL PATELLAR DESMOTOMY IN BUFFALOES (BOS BUBALIS) - Kassab, A; Badawy, A (Emirates Journal of Food and Agriculture, 2011)
The aims of the present study were to investigate the ultrasonographic appearance of the patellar ligaments in buffaloes before and after desmotomy. The medial, middle (intermediate) and lateral patellar ligaments, with upward fixation of the patella, were examined ultrasonographically in 12 adult buffaloes before and after medial patellar desmotomy. The results reveal that the ligaments were all of uniform echogenicity. The medial patellar ligament was visualized as highly echogenic circular structure, the middle patellar ligament as thick and triangular and the lateral patellar ligament was more echogenic structure and appeared flattened triangular in cross section. After surgery, there was slight increase in the thickness and width of the patellar ligaments especially the medial one. Ultrasonography will be useful as a complementary technique for examining the patellar ligaments of the buffalo.